A real space Moiré inversion technique and its practical applications in real space for lattice reconstruction - Bo Cui; Hongye Zhang; Miao Li; Dong Zhao; Huimin Xie; Zhanwei Liu (Theoretical and Applied Mechanics Letters)
Distinct physical properties emerge at the nanoscale in Moiré materials, such as bilayer graphene and layered material superposition. This study explores similar structural features within a second-generation nickel-based superalloy, unveiling potential formation mechanisms. Introducing the real space Moiré inversion method (RSMIM) for nanoscale imaging, combined with the transmission electron microscopy (TEM) nano-Moiré inversion method, we reveal spatial angles between specimen and reference lattices in 3D. Simultaneously, we reconstruct the Moiré pattern region to deepen us understand the phenomenon of Moiré formation. Focused on face-centered cubic structures, the research identifies six spatial angles, shedding light on Moiré patterns in the superalloy. The RSMIM not only enhances understanding but also expands 3D structure measurement capabilities. The RSMIM served to validate TEM nano-Moiré inversion results, ascertaining the spatial relative angle between lattices, and establishing a theoretical simulation model for Moiré patterns. This study marks a substantial step toward designing high-performance nanomaterials by uncovering dynamic Moiré variations.